Intratendinous platelet-rich plasma injection and percutaneous needle tenotomy in the treatment of hip tendinopathies: A retrospective study - David Levi; Yuchia Wang; Scott Horn; Sydney Campbell; Christa Ventura (Journal of Orthopaedic Reports)
Background: Both conservative and surgical treatment options for tendinopathies often have less than ideal outcomes. Platelet-rich plasma (PRP) has become an increasingly popular treatment option with only limited evidence for effectiveness. Methods: A retrospective review was performed of all consecutive patients undergoing PRP for hip tendinopathies during a three-year period in a single outpatient spine and musculoskeletal clinic. Each procedure was performed under ultrasound guidance with a concurrent needle tenotomy. Categorical data analysis was performed to determine percent of patients achieving at least 30 %, 50 %, and 80 % relief of pain as measured by NRS. Results: A total of 48 patients were included with an average follow period of 14 weeks. Seventy-seven percent of patient achieved at least 30 % improvement in pain by NRS (95 % CI: 63%–88 %), 65 % achieved at least 50 % improvement in pain (95 % CI: 49%–78 %), and 27 % achieved at least 80 % pain improvement (95 % CI: 15%–42 %). Conclusion: This retrospective study demonstrates relatively good outcomes for this novel treatment. The results of this single practice audit are similar to previously published retrospective and prospective trials.